Community Knowledge, Attitudes, and Beliefs about Complementary and Alternative Medicine in Magelang - Pratiwi, Anggi; Latifah, Elmiawati; Hapsari, Widarika Santi (Prosiding University Research Colloquium, 2021)
Complementary and alternative medicine (CAM) has been used by 70% of rural communities in Indonesia. Society is a group that is vulnerable to irrational use of CAM which can harm CAM users. This study aims to describe the level of knowledge, attitudes, and public beliefs about CAM in Magelang. The research method is descriptive quantitative using a cross-sectional research design conducted on 100 communities in Magelang using a questionnaire for data collection. Data analysis using SPSS 16.0. The data shows that Magelang people know the most about lime herbal therapy to treat cold and flu symptoms (83%), low knowledge about contraindications to ginseng herbal therapy (38%), and about the foreign term Ginkgo biloba (33%). The highest level of community agreement regarding CAM treatment methods must be known by doctors (33%), and the highest belief about the effects of complementary therapies is the result of suggestions (24%). The majority of Magelang people have a moderate level of knowledge (48%), good attitude (93%), very good attitude (7%), good belief (10%), and very good belief (20%) about complementary and alternative medicine (CAM). Strengthening regulations and socializing the use of CAM can be done to increase knowledge and behavior of CAM practices in a rational society.